Past ans present in a South African clip: Popular music and representations of the "new" South Africa among Afrikaner youths, the case of "De La Rey" - (:unkn) unknown (My University, 2015)
Preliminary extended version of a paper published under the title: « Le général ne répond pas... Chanson, clip et incertitudes : les jeunes Afrikaners dans la "nouvelle" Afrique du Sud », published in: L'Homme 215-216, juillet-décembre 2015 : 197-232 .In March 2006 a singer known as Bok Van Blerk released a CD titled "Jy praat nog steeds my taal" (You keep on speaking my tongue) in which a song alluded to the "naked flames" of Afrikaans and emphasised the Afrikaners' pride. The CD also contained a song speaking of a forgotten general who fought during the second anglo-boer war, "Koos" De La Rey. This song, and the video clip which accompanied it rapidly became extremely popular among Afrikaner youths and triggered intense debates. This text analyses the song (music and lyrics) as well as the clip and compare the results of the analysis to comments published in the press or posted on internet sites, comparison complemented by two non-directive interviews conducted with South African students. The outcome of this research confirms that feelings regarding the "new" South Africa which predominate among Afrikaner youths are uncertainty and ambivalence.
Keywords: African Research